Rettspolitisk mobilisering og strategisk sakførsel mot isolasjon i norske fengsler - Kjersti Lohne; Marte Rua (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Solitary confinement in prison and police detention has been a widespread criminal policy and human rights problem in the Scandinavian countries for decades. However, in recent years, there has been a significant legal mobilization in Norway whereby lawyers individually and collectively have challenged solitary confinement in the courts. This use of strategic litigation has been directed towards solitary confinement in police custody,  remand and during imprisonment. Based on qualitative interviews and documents, we analyze the organizational and legal strategy behind this legal mobilization, along with its effects and preconditions. We find that strategic litigation by lawyers has played an important role in the struggle against solitary confinement in Norway, but that it has benefited from – and played in tandem with – a legal and political opportunity structure consisting of national as well as international actors, processes, and legal frameworks. These findings raise the question of whether lawyers and civil society can contribute in similar ways in the other Scandinavian countries.